Pola Komunikasi Ibu dan Anak Disabilitas di Kecamatan Talaga Raya Kabupaten Buton Tengah - Wa Ode Risna Zaindra (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2023)
The role of communication is very important for social life, because basically communication is a basic human activity and is a dynamic transactional process that influences behavior. According to communication experts, there are many forms of communication such as interpersonal communication, intrapersonal communication, organizational communication, and others. Based on temporary observations in Talaga Raya District, Central Buton Regency, there are several children with disabilities. These disabled children experience mental retardation, growth and development and speech disabilities, hearing impairments, and physical disabilities, so they are quite slow, making communication less slow, compared to normal children in general. The method used in this research is a qualitative method using a descriptive approach. Their attitudes and behavior are not as cheerful as children in general and they also have difficulty communicating and interacting with other people. From this problem, researchers are interested in researching "Communication Patterns of Mothers and Children with Disabilities in Talaga Raya District, Central Buton Regency." The results of this research are that the communication patterns of mothers and children with disabilities in Talaga Raya District, Central Buton Regency are quite good, although a little passive. in carrying out this communication pattern. Because communication must be done with body language, be patient, speak with a loud voice and slow intonation and speak by repeating words. Apart from that, when a child with a disability is angry if the child's wishes are not followed, the mother must speak patiently because the mother must try to understand what the child means and learn about what the child with a disability wants.